2014
DOI: 10.1177/1350650114527922
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the variation of friction coefficients of human skin as a function of skin hydration and interfacial water films

Abstract: Human skin is characterised by a complex and highly variable friction behaviour. Although the variation of friction coefficients measured for skin depends on numerous parameters related to the skin itself, the surface in contact as well as contact conditions, water or sweat -either bound in the stratum corneum and manifest as skin hydration or in form of liquid films lubricating the interface -is the most important factor. Here, we analyse the variation of previous experimental data on the basis of the adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
1
36
0
2
Order By: Relevance
“…On smooth glass, small amounts of moisture are accumulated on the surface and thus remain in the immediate vicinity of the skin in contact. This situation probably leads to local changes in the interfacial conditions, combined with a sensitive influence on friction [27]. A smooth surface also provides effective occlusion of the skin and thereby facilitates sweating.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…On smooth glass, small amounts of moisture are accumulated on the surface and thus remain in the immediate vicinity of the skin in contact. This situation probably leads to local changes in the interfacial conditions, combined with a sensitive influence on friction [27]. A smooth surface also provides effective occlusion of the skin and thereby facilitates sweating.…”
Section: Methodsmentioning
confidence: 98%
“…If the real contact pressure is expressed as p r ¼ ðA=A r Þ U p, where A represents the apparent contact area and p the apparent pressure, the adhesion friction model becomes μ adh p ð Þ ¼ ðA r =AÞ U τ 0 =p þα. In this form, the model in specific cases allows to estimate ranges for the ratio A r =A and the parameters τ 0 and α from friction coefficients measured as a function of the apparent contact pressure [3,27]. The analysis of the results shown in Fig.…”
Section: Friction and Abrasion Mechanisms Of The Finger Pad On Smoothmentioning
confidence: 97%
“…9,15,[26][27][28][29][30] Given that skin is able to take up water, it is reasonable to assume that water should also change its morphology and surface properties. In order to analyze these changes over time, we have employed 3D laser scanning microscopy, which allowed us to observe the surface of a skin replica under high magnification and provided 3D information.…”
Section: Introductionmentioning
confidence: 99%
“…The friction behaviour of the medical textiles was investigated by means of apparative measurements using a validated mechanical skin model as well as in in-vivo friction measurements, in which subjects rubbed the skin of their volar forearm against textile samples (Rotaru et al, 2013). When varying the amount of interfacial water from dry to wet conditions it was found that the friction between skin and textiles at contact pressures between 1 and 1.5 kPa increased up to a factor of five and that the overall friction behaviour was in accordance with the adhesion friction model (Derler et al, 2014).…”
Section: Introductionmentioning
confidence: 54%